RESTORATIVE JUSTICE DALAM PERADAPAN HUKUM MODERN (Refleksi Nilai-nilai Agama Hindu) - Hartanto, Hartanto (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
Indonesia is a country of law that recognizes the existence of customary and religious law as a source of law. The daily practice of menusia is to communicate (naturally) but in this opinion and / communication often occurs speech that violates the rights of others or hurts other parties, then the potential for this conflict penetrates using spoken language on social media (internet). The regulation that regulates criminal acts related to defamation is Law No. 19 of 2016 concerning Electronic Information and Transactions, while the more general nature is the criminal code, which has